A Literature Review on the Integration of Ethno-STEAM in Science Learning through Local Potential: The Case of ‘Mi Lethek Bantul’ - Yuli Arti; Asri Widowati; Autchariya Krautharot (IJIS Edu : Indonesian Journal of Integrated Science Education, 2025)
This study is a literature study which is conducted to explore the incorporation of the Ethno-STEAM-based approach to learning science using local potential of 'Mi Lethek Bantul'. Ethno-STEAM is a learning approach that integrates Science, Technology, Engineering, Arts, and Mathematics, by integrating local cultural values as a learning environment.     . Mi Lethek as a traditional dish made of cassava flour embodies various simple concepts of science and technology that can be used in the learning process, e.g., physical and chemical changes, traditional biotechnology procedures, use of energy, and concepts of traditional tool engineering      It is demonstrated in the study that science learning based on the incorporation of the Ethno-STEAM approach using 'Mi Lethek Bantul' is fostering improved conceptual understanding of the students, in addition to fostering cultural awareness, creativity, critical and problem solving skills. Through this incorporation, there is the potential to develop contextualized, pertinent learning, and enhance the development of the character of the students and character literacy in the sciences. Hence, the application of Etno-STEAM drawn from local potential is a powerful strategy in holistic, sustainable learning in the sciences.